Optimizing Prowriting to Enhance Writing in EFL Context - Aulia Nisa' Khusnia (Universitas Islam Nahdlatul Ulama Jepara, 2021)
This study aims at investigating educational technology in writing. Prowriting is one of the application that used to support writing. It is a systematic system to support writing. It covers grammar, style, and summary reports. Therefore, it essential to use Prowriting in writing class. The mixed-method as a research design on quantitative and qualitative. Parallel design where both of data taken concurrently. The students of the non- English department, 25 students of Akademi Farmasi Kusuma Husada Purwokerto got involved in this research. Writing criteria are also measured as interrater in this research. It results in the means of all requirements. Globally, Purpose, Audience, Coherence, and Unity are 2.46,2.3,2.3, 2.3, and 2.13. Besides, the writing captured from Prowriting is grammar, style, and spelling. Those are illustrated in the summary report. Moreover, it describes students' engagement, improved writing results, self-learning (learning at the own pace), and the educational technology system's progress.